Odd-even effect dependence on the excitation energy in low energy fission - Mirea M. (EPJ Web of Conferences, 2017)
An inversion of the odd-even effect was observed experimentally in cold fission: the odd-odd fragmentation yields are favored over the even-even ones for excitations energies of the fragments smaller than 4 MeV. This effect is linked to the important problem of quasiparticle excitations during the dynamical evolution of the nuclear system from its ground-state configuration up to scission. An explanation based on the Landau-Zener promotion mechanism generalized for superfluid systems is offered for the inversion of the odd-even effect. In principle, the even-even fission products cannot be produced at very low excitation energies due dynamical quasiparticle excitations produced in the avoided- level-crossing regions. These excitations are produced with a large probability when the nuclear system deforms slowly.